A theoretical project evaluation framework for urban transportation network improvement in the context of random utility theory - Kikuchi, Tatsuto; Morisugi, Hisa; Fujiwara, Okitsugu; Shrestha, Ram M.; Keidanren (Bangkok : Asian Institute of Technology, 1997)
Transportation project gives influence to the market mechanism. The influence is not only due to the transportation fare but also externalities such as congestion and scale economy. Congenstion results from the change in the transportation time requirement, and the change in scale economy from households relocation through a project. This thesis is one of the attempts to measure the benefit due to the influence of a project including externalities. First, this thesis aims to construct a Walrasian multi-regional general equilibrium model, incorporating externalities. The households make location choice through an implementation of a project, subject to random utility theory, and achieve the expected maximum utility level. The change in households' utility level is measured as the social net benefit. To grasp the influence of a project, several measurements are derived in the context of the model. Then, finally, this thesis proposes suggestion to the practical project evaluation for urban transportation project.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1997
Keywords: Urban transportation